Immunohistochemical study of polycystin-1 in dentigerous cysts - Jaishlal Mariachelliah Nadar Singarayan; Thavarajah Rooban; Elizabeth Joshua; Umadevi Moduali Rao; Kannan Ranganathan (Wolters Kluwer Medknow Publications, 2014)
Background: The alterations involved in step-wise transformation of a dental follicle to dentigerous cyst (DC) is not clearly known. Primary cilium and its protein have been hypothesized to be associated with DC. Mutation of a ciliary protein, polycystin-1 (PC1) is associated with autosomal dominant polycystic kidney disease. This study was performed to assess the immunohistochemical expression of PC1 between DC and postfunctional follicular tissue (PFFT). Materials and Methods: Thirty-one consecutive PFFT and 15 DC formed the study group. The PFFT and DC tissues were stained with antibody against PC1. Statistical Package for Social Service was used to analyze data. Descriptive statistics and Student's Chi-square test were appropriately used. P ≤0.05 was taken as significant. Results: Fifteen DC (100%) and 7 (22.58%) PFFT were positive for PC1. The difference was statistically significant (P = 0.000). PC1 expression was observed in the cytoplasm with varying intensity. Discussion and Conclusion: All PC1 positive epithelial cells' cytoplasm stained diffusely. Abnormal cytoplasmic expression of PC1 in all positive epithelial lining indicates that the PC1 probably is associated with cystic transformation.